Sulfadiazine Plus Clindamycin and Trimethoprim / Sulfamethoxazole Plus Clindamycin Versus Standard Treatment for Therapy of Ocular Toxoplasmosis - Behnaz F, Maanaviat M.R, Mohammadzadeh M, Miratashi A.M (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare efficacy and side effects of clindamycin plus sulfadiazine and Trimethoprim / sulfamethoxazole plus clindamycin, with pyrimethamine plus sulfadiazine for treatment of toxoplasma chorioretinitis. Material and Methods: Descriptive case series study. Results: Of 79 toxoplasma retinochoroiditis patients, 41, 16 and 22 patients were treated with standard treatment, clindamycin plus sulfadiazine (group1) and Trimethoprim / sulfamethoxazole plus clindamycin (group2) respectively. Visual acuity of three groups improved similarly, with no significant difference between them (6/21 ± 6/32, 6/24 ± 6/70 and 6/21 ± 6/37 in standard group, groups 1and 2 respectively) (PV: 0.496). Decrease in activity of lesions began 27.2 ± 7.62, 27.8 ± 12.6 and 28.6 ± 8 days after treatment in standard group, group 1 and 2 respectively (PV: 0.572). Vitreal inflammation also began to decrease similarly in three groups (PV: 0.152). The frequency of adverse drug effects leading to treatment interruption was highest in group 2 (14%) with mild side effects observed in 31.7% of them. Conclusion: The efficacy of 3 regimens was similar, but highest frequency of side effects was associated with trimethoprim / sulfamethoxazole plus clindamycin, if careful monitoring of adverse drug effects is impractical it is not recommended.